Innovative activity in the context of the federal districts of the Russian Federation: current state and directions of development - E. A. Pogrebtsova (Вестник университета)
In modern realities the development of the country is impossible without the introduction of innovative developments in production. Therefore, identifying the level of innovation activity in the context of all federal districts makes it possible to assess the capabilities of each subject of the country and based on this monitoring to form an innovation development strategy. Considering certain indicators which characterize the productive component of the innovation potential, the author conducted a comparative assessment of the federal districts of the Russian Federation, identified trends and directions of development. Conclusions are drawn about the problems and opportunities of innovative development. The purpose of the study is to determine the innovative activity development direction of the Russian Federation in the main federal districts. To achieve the goal, the following tasks were identified: to assess the volume of innovative goods produced by federal districts; to define the costs of this activity; to find the factors constraining innovative development.